Notes Toward a Postmodern Principle. Issue 1 (6th February 2018) - Hooper, Nicholas
Abstract : The current approach to statutory interpretation in Canada, viz., the ubiquitous "modern principle, " is an empty rhetorical gesture that masks the contingent, subjective nature of language and naturalizes institutionally sanctioned definitions. Since the late-nineties, virtually every relevant decision cites the same passage as methodology, positing the discoverability of objective textual meaning by looking to things like the "ordinary sense" and "intention of Parliament." This is theoretically incoherent and incompatible with most credible understandings of language and interpretive subjecthood. This paper begins with a critical reading of each directive in the "modern principle" to demonstrate the normative force of its outdated approach. After discussing the legitimizing function of an ostensibly consistent method that elides the difficulties of linguistic meaning, I conclude with a preliminary discussion on the possibility of progress—or the idea of (literally) a postmodern principle of statutory interpretation.